The effect of information technology-based services, customer trust, and perceived comfort of use on brand switching prepaid electric products - Priangan Sari, Ni Luh Putu Utari; Pemayun, A. A. Gede Putra (Review of Management, Accounting, and Business Studies, 2022)
This study aimed to determine the effect of information technology-based services, customer trust, and perceived comfort of use on brand-switching prepaid electricity products. The population in this study was 74,691 prepaid electricity customers and 100 samples were taken. The data in this study were obtained by questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study indicated that information technology-based services have a positive and significant effect on brand switching of prepaid electrical products with a regression coefficient of 0.265 is positive, a value of 0.006 is less than 0.05 (0.006 <0.05). Customer trust had a positive and significant effect on brand switching of prepaid electrical products with a regression coefficient of 0.414 is positive, and a value of 0,000 is less than 0.05 (0,000 <0.05). Perceived comfort of use had a positive and significant effect on brand switching of prepaid electrical products with a regression coefficient of 0.274 with a positive value, a value of 0.013 less than 0.05 (0.013 <0.05). Then, the information technology-based services, customer trust, and perceived comfort of use together had a positive and significant effect on the brand switching of prepaid electrical products by 0,000 less than 0.05 (0,000 <0.05).